Penerapan Undang-Undang Nomor 3 Tahun 1997 Tentang Pengadilan Anak Dalam Kasus Pencabulan Di Wilayah Hukum Pengadilan Negeri Boyolali - Azis Indro Suharto (Verstek, 2013)
This research aims to find out the indecency committed by the minor case in Boyolali First Instance Court jurisdiction. The objective is to find out the constraints the judge faces as well as the attempt of coping with such the constraints. The child is not the same as adult so that in the procedural process should be observed that it is different from that for adult. There should be a special court with the rules different from that of general court.This study was an empirical research type that was normative descriptive in nature using a case study. The location of research the writer used was Boyolali First Instance Court. The type of data used included primary and secondary data. Techniques of collecting data used were observation, interview and library study on both book and legislation. Those primary and secondary data were then analyzed qualitatively so that an accurate description was achieved concerning the result  of research. Based on the research, it could be found that in the process of resolving the indecency crime with minor perpetrator in Boyolali First Instance Court, the judge handling the case had referred to the Act No.3 of 1997 about the Child Court. Thus, in this enactment of act, a strong legal foundation is obtained to differentiate the treatment to the child involved in a crime. Such the treatment differentiation was began during the examination process from investigation level to sentencing process in the trial that was conducted specifically corresponding to what governed in Child Trial Act.      Keywords: Procedural, child trial, indecency, child.